HUBUNGAN KEBISINGAN DENGAN GEJALA STRES KERJA DI BAGIAN POWER HOUSE PT. HUMBAHAS BUMI ENERGI KABUPATEN HUMBANG HASUNDUTAN TAHUN 2015 - rafika lumban gaol; kalsum *; eka lestari mahyuni (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Work environment is one of the main sources of potential health hazard. Noise is one of the factors found in work environment. It can cause someone who is exposed to noise to be in the state of stress.The research was an analytical survey with cross sectional method. The population was 12 employees who worked in the Power House division of PT. Humbahas Bumi Energi, using total sampling technique. The result of the research showed that the average noise in the Power House division of PT. Humbahas Bumi Energy was 95 dBA (exceeding the threshold of 85 dBA). The result of work stress symptom showed that 3 respondents (25%) were in mild stress category, 7 respondents (58,3%) were in moderate stress category and 2 respondents (16,7%) were in severe stress category. The result of Spearman correlation test showed that the significance value (2-sided) was 0,001 (p ≤ 0,05) which indicated that there was significant correlation between noise exposure and work stress symptom. The result for analytic test in the Power House of PT. Humbahas Bumi Energi at the r value = 0,851 and contribution among the variables was 72,42%. The conclusion of the research was that there was significant correlation between noise exposure and work stress symptom in the employees in the Power House division of PT. Humbahas Bumi Energi. The noise which was above the thanthreshold was reduced by installing silencer like elastic bolster on the machine or lining the wall, ceiling and the floor with noise absorbing device. Keyword : Noise, Power House, Work Stress Symptom